Toxicity Test Pediocin N6 Powder Produced from Isolates Pediococcus Pentosaceus Strain N6 on White Mice - Ketaren, Nurjama'yah Br.; Marlida, Yetti; Arnim, Arnim; Yuherman, Yuherman; Rusmarilin, Herla (Journal of Food and Pharmaceutical Sciences, 2016)
Pediocin N6 powder is a bacteriocin the heat resistant derived from isolates Pediococcus pentosaceus strain N6. These were isolated from water source heat Rimbo Panti West Sumatra. Pediocin N6 powder has high antimicrobial activity, so the potential to be used as biopreservatif on meat and food processing industry which involves heating. Toxicity test was conducted to determine the effects of the toxic effect of a single dose of oral Pediocin N6 powder in test animals male white mice to determine the LD50 and see changes in body weight of mice for 15 days of treatment. Changes in body weight of mice was determined by using non factorial experiment in a completely randomized design consists of 4 treatments and 5 replications. The test animals were divided into 4 groups and each treatment consisted of 5 mice. The treatments tested consisted of Pediocin N6 powder 5000 mg/kg body weight, 10,000 mg/kg body weight, 15,000 mg /kg and 20,000 mg /kg body weight of mice. The test results showed that the Pediocin N6 powder up to a dose of 20 000 mg/kg in a single oral dose administration, there are no death of mice to 15 days of treatment. Based on the LD50 value of a single oral dose can not be calculated, based on it can be stated LD50 value pseudo Pediocin N6 powder greater than 20,000 mg /kg in male mice. The average changes in body weight of mice at a dose of Pediocin N6 powder treatment of up to 20,000 mg/kg every 2 days weighing from day 1 to day 15 of 2.1 gr. Based on these tests Pediocin N6 powder safe used as industry biopreservatif on meat and food processing involves heating.Key word: Toxicity Test, Pediocin N6 Powder, White Mice, Biopreservatif on Meat